Six-country psychometric comparison of women responses to the Depression Anxiety Stress Scale (DASS) and the Child and Adolescent Behaviour Inventory (CABI) across cultures and time - Calderón Alfaro, Francisco Antonio; Lachman, Jamie; Ward, Catherine L.; Han, Qing; Jocson, Rosanne; Kunovski, Ivo; Eagling-Peche, Stephanie; Juhari, Rumaya; Okop, Kufre; Reyes, Jennel; Babii, Viorel; Cluver, Lucie; et al. (Elsevier, 2025)
Background: The Depression Anxiety Stress Scale (DASS) and the Child and Adolescent Behaviour Inventory (CABI) are freely accessible tools used to assess depression and externalizing symptoms, respectively. There is limited psychometric evidence on how these scales hold over time and across cultures. This study aims to evaluate the internal structure of both scales and their invariance across six countries and over two timepoints. Methods: Data from the ParentChat Pilot Study included information from 566 adults (85.51 % female) with children aged 2 to 17. Only female data from North Macedonia, Malaysia, Moldova, Montenegro, Philippines, and South Africa were used. Confirmatory factor analysis was employed to assess invariance of each construct. Results: At baseline, the DASS depression subscale achieved scalar invariance across five countries (CFI = 0.973, TLI = 0.956, RMSEA = 0.060, SRMR = 0.069) and across timepoints (CFI = 0.990, TLI = 0.979, RMSE = 0.037, SRMR = 0.034). The CABI extract achieved scalar invariance across two countries (CFI = 0.968, TLI = 0.963, RMSEA = 0.068, SRMR = 0.085) and across timepoints (CFI = 0.983, TLI = 0.980, RMSEA = 0.044, SRMR = 0.067). Limitations: Small sample sizes, disproportionate female sample, and use of subscales or item extracts may limit generalizability. The scales were also not validated for all age groups used. Conclusions: The study provides evidence of validity for the internal structure of the DASS and CABI extracts across cultures and over time. These findings support the use of these open-access tools in resource-limited settings to promote local research.